1994
DOI: 10.1002/ajmg.1320530406
|View full text |Cite
|
Sign up to set email alerts
|

Social‐emotional and behavioral adjustment in children with Williams‐Beuren syndrome

Abstract: In children with Williams-Beuren syndrome (WBS), disturbed behaviors (neurotic, antisocial, and hyperactive) [Arnold et al., 1985: Dev Med Child Neurol 27:49-59; Udwin et al., 1987: J Child Psychol Psychiat 28:297-309] have been described. To study the behavior disturbances and social-emotional adjustment in children with WBS, a group of N = 19 patients was compared with a control group, matched for age, gender, and nonverbal reasoning abilities. Parents were asked to assess the children's behavior in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 22 publications
4
66
0
Order By: Relevance
“…They are no better than wellmatched controls with LID in on-line tasks that tap the ability to decode social-affective information, just as they are no better in socialcognitive tasks (Tager-Flusberg & Sullivan, 2000). Nevertheless, children and adults with WMS appear to have a unique social phenotype characterised by unusual friendliness, especially toward strangers, and a warm empathic manner in engaging with others (Dykens & Rosner, 1999;Gosch & Pankau, 1994;Jones et al, 2000). It remains to be seen whether this phenotype is best interpreted in terms of personality variables (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are no better than wellmatched controls with LID in on-line tasks that tap the ability to decode social-affective information, just as they are no better in socialcognitive tasks (Tager-Flusberg & Sullivan, 2000). Nevertheless, children and adults with WMS appear to have a unique social phenotype characterised by unusual friendliness, especially toward strangers, and a warm empathic manner in engaging with others (Dykens & Rosner, 1999;Gosch & Pankau, 1994;Jones et al, 2000). It remains to be seen whether this phenotype is best interpreted in terms of personality variables (cf.…”
Section: Discussionmentioning
confidence: 99%
“…At the outset, interest in the syndrome was sparked by case studies of unusual social and linguistic behaviour (e.g., Bellugi, Bihrle, Neville, Jernigan, & Doherty, 1992;Bellugi, Marks, Bihrle, & Sabo, 1988;Udwin, Yule, & Martin, 1987), which led researchers to search for spared abilities in the context of general mental retardation and of severe specific cognitive deficits in visual-spatial construction skills. This paper focuses on the social component of the WMS profile, addressing the question of whether the unusual sociability and friendly personality characteristic of people with this neurodevelopmental disorder (Gosch & Pankau, 1994;Jones et al, 2000;Mervis & KleinTasman, 2000) is associated with relatively spared abilities in decoding mental state information from nonverbal facial cues.…”
mentioning
confidence: 99%
“…Research has demonstrated that WS is associated with deficits in adaptive behavior [14]- [16]. Researchers found that children with WS obtained significantly lower scores in adaptive behavior compared to their IQ-and chronological age (CA) matched counterparts with nonspecific intellectual disability [17]. Another study also found that, despite having a similar degree of general cognitive impairment, relatively few individuals with WS were able to attain a reasonable level of independence, or cope with the demands of employment when compared to groups of adults with other intellectually disabling genetic disorders (i.e., Down syndrome and Prader-Willi syndrome) [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, persons with WS are at increased risk for significant, longterm problems with excessive anxiety and over-arousal compared with intelligence quotient (IQ)-matched controls (Davies et al, 1998;Dykens, 2003). Individuals with WS also demonstrate excessive linguistic affect during conversations and when giving narratives Reilly et al, 2004) and heightened emotional reactions to music and certain classes of noise (Gosch and Pankau, 1994;Einfeld et al, 1997). In a preliminary functional magnetic resonance imaging study from our group (Levitin et al, 2003), we showed that, compared with controls, individuals with WS had significantly increased (right) amygdala activation during music processing compared with controls, thus providing a putative neural correlate of increased emotional "expressiveness" observed within the contexts of both music (Hopyan et al, 2001) and language (Losh et al, 2000) in affected individuals.…”
Section: Introductionmentioning
confidence: 99%